Законність та правовий характер адміністративного примусу - Дембіцька, Сусанна Леонідівна; Дембицкая, Сусанна Леонидовна; Dembickaja, S. (Одеса : Юрид. л-ра, 2014)
Based on comparative analysis of administrative law and theoretical positions on coercion as a means of law, its place, the classification of administrative enforcement, are the main characteristics, its main assets: warning, suspension, administrative sanctions.
Дембіцька С. Л. Законність та правовий характер адміністративного примусу / С. Л. Дембіцька // Актуальні проблеми держави і права: зб. наук.пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.]; МОН України, НУ ОЮА. – Одеса: Юрид. л-ра, 2014. – Вип. 71. - С.25-31.
Keywords: законність; примус; адміністративний примус; методи впливу; законность; принуждение; административное принуждение; методы влияния; legality; compulsion; administrative enforcement; impact of techniques